1995
DOI: 10.1093/oxfordjournals.annonc.a059357
|View full text |Cite
|
Sign up to set email alerts
|

Further chemotherapy versus low-dose involved-field radiotherapy as consolidation of complete remission after six cycles of alternating chemotherapy in patients with advanced Hodgkin's disease

Abstract: No statistically significant differences in treatment efficacy were detected between 20 Gy IF radiotherapy and 1X (COPP + ABVD) chemotherapy following CR after six cycles of alternating chemotherapy in patients with advanced-stage HD. However, limited observations in a non-randomized cohort indicate that patients without consolidation treatment of CR after 6 cycles of chemotherapy may have an elevated risk of relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Current therapies fail to cure about one third of patients with HL, and a similar proportion of patients may be overtreated (18)(19)(20). A precise early-prediction tool of response to therapy should be able to discriminate patients who could be cured with conventional therapy or even less intensive or toxic regimens from patients who need to switch to more aggressive treatment strategies that could improve outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Current therapies fail to cure about one third of patients with HL, and a similar proportion of patients may be overtreated (18)(19)(20). A precise early-prediction tool of response to therapy should be able to discriminate patients who could be cured with conventional therapy or even less intensive or toxic regimens from patients who need to switch to more aggressive treatment strategies that could improve outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Three subsequently reported randomized trials examined the usefulness of radiation for patients in complete remission after chemotherapy for advanced-stage Hodgkin lymphoma and found no significant impact. [23][24][25] Although one study of similar design showed contradictory results, it primarily focused on pediatric patients and patients with limited-stage disease. 26 Overall, the negative long-term effects of radiation appear to outweigh any benefits for the usual patient with ad- vanced-stage disease.…”
Section: Advanced-stage Hodgkin Lymphoma: Key Studiesmentioning
confidence: 99%
“…With a median follow-up of eight years, there were no statistically significant differences in relapsefree or overall survival (Fabian et al 1994). The GHSG randomized patients with stage III or IV disease in complete remission by computed tomographic assessment after six cycles of COPP/ABVD to two more cycles of chemotherapy or low-dose (20 Gy) IFRT, and this study demonstrated no difference in relapse rate between the two arms (Diehl et al 1995). A GELA study assessed the role of more extensive radiotherapy (subtotal nodal or total) versus two more cycles of chemotherapy in stage III/IV patients having achieved a complete or very good partial remission (≥ 75% size reduction) with six cycles of either MOPP/ABV or ABVPP.…”
Section: Role Of Radiotherapymentioning
confidence: 92%